Sucrose specificTRAP markers as genus and species specific markers in Saccharum and Erianthus spp. - Hemaprabha, G.; Lavanya, D. Leena (The Indian Journal of Genetics and Plant Breeding, 2016)
Sucrose specific candidate genes were used to identify species specific markers through Target Region Amplification Polymorphism (TRAP) based on a study involving nineteen Erianthus sp., Saccharum officinarum and S. spontaneum clones. In this study, 12 primer combinations comprising of the forward primers of four sequences of sucrose metabolizing genes and reverse primers of three arbitrary sequences were used to amplify the DNA samples of the species clones. A total of 296 bands within a size range of 38 bp to 1216 bp were detected. Out of these, 256 were polymorphic (86.49%) and 10 out of 12 combinations revealed more than 80% polymorphism.There were five Erianthus specificTRAP markers (SuSy + Arb3108, SuSy + Arb3260, SuPS(a) + Arb1155, SuPS(a) + Arb2370 andSAI + Arb3107) that would help in identifying intergeneric hybrids in nobilization process. Eight Saccharum specific markers (SuSy+Arb2144, SuSy+Arb3135, SuPS(a)+Arb1141, SuPS(a)+ Arb1518,SuPS(a)+Arb1628, SuPS(a)+Arb2212,SuPS(a)+Arb2282 and SuPS(b)+Arb1492 would enable detecting Saccharum genome during nobilization process especially when Saccharum is used as paternal parent. A marker specific to S. officinarum (SuSy+Arb1960) owes promise as a marker linked to sucrose content, being present in all sucrose rich clones belonging to S. officinarum and absent in low sucrose forms of Erianthus and S. spontaneum.